2022
DOI: 10.1038/s41598-022-07927-5
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of physical activity after spinal cord injury

Abstract: Physical activity is a powerful modifiable risk factor for disease and mortality. Physical activity levels in people with spinal cord injury (SCI) have not been quantified relative to uninjured individuals in a large population-based sample. We aimed to quantify and compare physical activity in people with and without SCI, and to examine the associations between physical activity, lifestyle, and socioeconomic factors. The 2010 Canadian Community Health Survey (n > 57,000) was used, which includes three meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A national health survey by the Centers for Disease Control and Prevention in 2020 [46] determined that only 24.2% of adults aged 18 and over met the physical activity guidelines for Americans for both aerobic and muscle-strengthening activities (150 min per week of moderate-intensity aerobic exercise and muscle strengthening exercises to the major muscle groups twice per week) [46]. Individuals with SCI perform only 35-40% as much exercise as the largely sedentary able-bodied population, demonstrating the extreme lack of physical activity in the SCI population [47,48]. Recently, Tui et al [49] completed a qualitative study concerning the motivations and barriers that limit adherence to exercise programs for individuals with SCI.…”
Section: Exercise Adherencementioning
confidence: 99%
“…A national health survey by the Centers for Disease Control and Prevention in 2020 [46] determined that only 24.2% of adults aged 18 and over met the physical activity guidelines for Americans for both aerobic and muscle-strengthening activities (150 min per week of moderate-intensity aerobic exercise and muscle strengthening exercises to the major muscle groups twice per week) [46]. Individuals with SCI perform only 35-40% as much exercise as the largely sedentary able-bodied population, demonstrating the extreme lack of physical activity in the SCI population [47,48]. Recently, Tui et al [49] completed a qualitative study concerning the motivations and barriers that limit adherence to exercise programs for individuals with SCI.…”
Section: Exercise Adherencementioning
confidence: 99%
“…On the lower end, Tasiemski et al found that only 20% of 985 people with SCI in the UK performed regular PA of 2 h/ week, and 53.3% reported no regular PA [10]. Furthermore, several other studies have indicated that the majority of individuals with SCI do not perform regular PA [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Advancement in medicine and science has resulted in the increased survivability of individuals who sustain a traumatic spinal cord injury (SCI), and a notable shift in healthcare focus towards managing chronically acquired diseases, particularly cardio-metabolic disease (CMD). A significant contributing factor to CMD in chronic SCI is the complex interplay of physical inactivity [1,2] altered body composition [3][4][5][6], and metabolic dysfunction [7,8] due to the neurological impairment. The resultant prevalence of conditions such as obesity [9][10][11], dyslipidemia [12][13][14][15], and insulin resistance [16][17][18], which often cluster into so-called cardio metabolic syndrome, constitute leading causes of mortality and morbidity in the population.…”
Section: Introductionmentioning
confidence: 99%